المسوحات والتنقيبات الاثرية فى فلسطين والوعى لأبعادها منذ منتصف القرن التاسع عشر حتى الحرب العالمية الاولى - الشلبي، سهيلا سليمان; العدوان، شادية حسن (الجامعة الأردنية - عمادة البحث العلمي, 2011)
شكلت التنقيبات الأثرية ركيزة أساسية ومهمة في مسألة تثبيت الادعاءات الصهيونية بأرض فلسطين أو دحضها، حيث استخدمت منذ قرون لغايات مختلفة من قبل أطراف متعددة، ففي حين ربطت الدول الغربية أطماعها السياسية والاقتصادية في المنطقة بغاية دينية تتمثل في إثبات ما جاء في التوراة، جاءت الصهيونية لتوظف حلم اليهود في العودة إلى أرض الميعاد وأرض الأجداد لتحقيق مكسب سياسي يتمثل في إقامة دولة يهودية/ صهيونية في فلسطين، مع إمكانية توسيعها إلى المناطق المجاورة. وانطلاقاً من ذلك، شهدت فلسطين والبلاد العربية المجاورة- وإن كانت بدرجة أقل- حركة مسح/ تنقيب واسعة من قبل البعثات الأثرية الأوروبية بشكل عام والبريطانية على وجه الخصوص. \ ولكن هذا الاهتمام والنشاط لم يجد ردة فعل ووعي عربي أو عثماني يماثله بالكم والنوع، واقتصر الأمر على ردود فعل متفرقة وموسمية لم تنطلق من خطة منظمة، إذ اقتصرت إثارة الموضوع على حوادث معينة وفي فترات متفرقة لم تكن تنطلق من وعي منظم بحيث تشن حملة متواصلة على مثل هذه التنقيبات وما يراد منها. كما لم يكن هناك وعي لأبعاد عمليات التنقيب، ودور الصهيونية فيها وما ترمي إليه من توظيف التاريخ لخدمة قضيتهم. Archaeological excavations represent an essential and important pillar for the issue of confirming or refuting the Zionist claims to the land of Palestine. Different parties have used them for centuries to achieve various goals. While Western states associated their economical and political ambitions in the area with religious objectives represented in confirming what is stated in the Bible, Zionism came to employ the dream of the Jews to return to the Promised Land and to the land of their ancestors in order to achieve a political benefit represented in establishing a Jewish/Zionist state in Palestine, with the possibility of expanding it into nearby areas. As a result, Palestine and the neighbouring Arab states – albeit to a lesser degree – witnessed large-scale survey and excavation by European archaeological expeditions in general and by British expeditions in particular. \ However, this interest and activity did not find any similar Ottoman or Arab reaction or awareness in terms of quality and quantity. There were only sporadic and occasional reactions that did not belong to an organized plan. The reaction was restricted to specific events at different times that did not stem from an organized awareness in order to launch a continous campaign against such excavations and their objectives. Moreover, there was no awareness of the dimensions of the excavations and the role of Zionism in attempting to employ history serve its cause.
Keywords: الصهيونية -- فلسطين -- المواقع الاثرية -- التنقيب عن الاثار -- الاكتشفات الاثرية -- القرن التاسع عشر -- اليهود -- الصراع العربى الاسرائيلى -- الدول الاوروبية